JOURNAL MAKING IN INSTRUCTION (TEACHING), RESEARCH EXTENSION WORK - Judith F. Balares-Salamat (Soegijapranata Catholic University, 2006)
This paper focuses on the advantageous use of journal in instructional, extension and research work. With the current trend of teachers involvement in three — instruction, extension, and research — sometimes four (including production) functions, journal-making process can never be underestimated. From simple reflective statements and insights to more analytical and in-depth viewpoints regarding the events of the day, or the fieldworks data gathered in the field, until the process of writing and re-writing the actual output, journal making helps attain what is called as intersubjectivity and multidisciplinarity. This makes a teacher, community/ extension worker, or researcher, a participant to the whole process of development.